Different traits shape winners and losers in urban bird assemblages across seasons - Riccardo Alba; Fabio Marcolin; Giacomo Assandri; Luca Ilahiane; Francesca Cochis; Mattia Brambilla; Diego Rubolini; Dan Chamberlain (Scientific Reports)
Abstract Urbanisation is a major driver of global biodiversity decline, profoundly affecting animal communities. While most studies on bird communities have primarily focused on the breeding season, we aimed to identify species responses and their associated traits by adopting a stratified design and using a multi-season approach considering a gradient from highly urbanised city centres to the urban–rural fringe across six Italian cities. We found that bird assemblages exhibited different responses to urbanisation according to season. Winners (i.e. species positively affected by urbanisation) were characterised by traits such as colonial nesting, high productivity and longevity. In winter, these species displayed generalist foraging strategies and solitary behaviour. Losers (i.e. species negatively affected by urbanisation) tended to be insectivorous, ground-nesting and short-distance migratory species. Interestingly, intra-specific variations emerged, with wintering populations of some species exploiting highly urbanised areas despite not breeding there. Urban adapters, although not strictly winners, displayed resilience by navigating a range of urban conditions, effectively exploiting intermediate levels of urbanisation. This study provides novel insights into the complex ecological dynamics occurring within the urban matrix in different seasons. Our findings emphasise the importance of adopting a multi-season approach in research and urban planning to better understand species responses and develop more effective, sustainable strategies for biodiversity conservation in urban environments.